2007
DOI: 10.1103/physrevb.76.174116
|View full text |Cite
|
Sign up to set email alerts
|

Association of oxygen vacancies with impurity metal ions in lead titanate

Abstract: Thermodynamic, structural, and electronic properties of isolated copper and iron atoms as well as their complexes with oxygen vacancies in tetragonal lead titanate are investigated by means of first principles calculations. Both dopants exhibit a strong chemical driving force for the formation of M Ti − V O ͑M =Cu,Fe͒ defect associates. The most stable configurations correspond to a local dipole aligned along the tetragonal axis parallel to the spontaneous polarization. Local spin moments are obtained and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 49 publications
10
100
0
Order By: Relevance
“…The activation energies of the oxygen vacancies migration were assessed to amount to (0.90±0.05) eV, (0.84±0.05) eV and (0.052±0.05) eV, respectively for BPT, BPTC(1 %) and BPTC(0.1 %) ceramics. The activation energy of free oxygen vacancy migration in ferroelectric perovskite oxides has been reported to be of 0.8-1 eV [51,52] thus we can relate the high-temperature electric conduction determined for BPT and BPTC(1 %) ceramics to the process of oxygen vacancies migration. As the distribution of the oxygen vacancies in the lattice has been considered in the tetragonal phase of the ferroelectric perovskites only [26,50,52] it is hard to discuss the lowering of the activation energy for BPTC(0.1 %) since the energy landscape of oxygen and probably also Pb vacancies is uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The activation energies of the oxygen vacancies migration were assessed to amount to (0.90±0.05) eV, (0.84±0.05) eV and (0.052±0.05) eV, respectively for BPT, BPTC(1 %) and BPTC(0.1 %) ceramics. The activation energy of free oxygen vacancy migration in ferroelectric perovskite oxides has been reported to be of 0.8-1 eV [51,52] thus we can relate the high-temperature electric conduction determined for BPT and BPTC(1 %) ceramics to the process of oxygen vacancies migration. As the distribution of the oxygen vacancies in the lattice has been considered in the tetragonal phase of the ferroelectric perovskites only [26,50,52] it is hard to discuss the lowering of the activation energy for BPTC(0.1 %) since the energy landscape of oxygen and probably also Pb vacancies is uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…For example, this setup corresponds to dopant-oxygen vacancy complexes in transition metal doped perovskites. It has been reported [15][16][17] that such complexes form immediately during the synthesis process, that they have much slower relaxation times than the free dipoles related to the ferroelectric soft mode, and that different relative orientations towards the spontaneous polarization of the host ferroelectric material are possible. In the present study, we assume fixed defect dipoles, which is a rather realistic approximation at low and ambient temperatures during the time span of a typical ECE measurement, cf.…”
Section: Polar Complexesmentioning
confidence: 99%
“…2,4,6,18,19 In particular, experimental and theoretical investigations reveal the important role of transition metal doping on fatigue behavior in ferroelectric perovskites. 12,[15][16][17] It has been found that an internal bias field builds up in field polarized (poled) Cr doped BTO, which could be related to the alignment of defect dipoles with the overall polarization. 12 In this context Erhart and co-workers performed detailed ab initio based transition state theory simulations on transition metal doped perovskites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations